MODEL TERINTEGRASI PENGELOLAAN GURU DALAM MEWUJUDKAN PEMBELAJARAN BERKUALITAS DI SEKOLAH DASAR ISLAM - Qomaruddin Hidayat; Teguh Prawiro; Fatkhul Mubin (Andragogi: Jurnal Pendidikan Islam dan Manajemen Pendidikan Islam, 2025)
This study employs a qualitative case study approach, with data collected through documentation analysis, interviews, and observations. The data were analyzed thematically using content analysis, including data reduction, data presentation, and conclusion drawing. The findings reveal that the teacher management model at SD Khalifah Krukut Depok is implemented through several stages: needs analysis, recruitment (selection), orientation and training, assignment, in-service training, coaching, and evaluation. Teacher performance is monitored and assessed through academic and non-academic supervision activities conducted once every semester. Learning program planning is conducted at the beginning of each academic year through structured teacher meetings. The teacher management model at SD Khalifah Krukut is characterized by a systematic, programmed, holistic, and integrated approach, which includes training, workshops, mentoring, and monitoring—contributing significantly to improving the quality of learning. However, several obstacles hinder this process, such as inadequate infrastructure, limited teacher competence and motivation, weak work ethic, and the lack of professional development activities led by field experts. To overcome these challenges, teachers have engaged in internal and external seminars, collaborative group discussions, and peer teaching to foster continuous improvement in classroom instruction.